Tourism Mobility : The Visual Journey to Malaysian UNESCO World Heritage Sites - Salmiah, Binti Abdul Hamid; Qistina Donna, Lee Abdullah; Teo, Miaw Lee (UNIMAS PUBLISHER, 2018)
The research project entitled “Tourism Mobility: The Visual Journey to Malaysian UNESCO World Heritage Sites” aims to evaluate reliability of signages of selected Malaysian UNESCO World Heritage Sites. In the process of fulfilling the research objectives, a collection of images showcasing the beauty and diversity of the sites is produced. It is also the aim of this research to analyze the signages at UNESCO sites and the outcomes are documented in the responses of the tourists visited the sites. Hence, the production of this book that signifies the reliability of tourism mobility through signages, is presented as a source of information for tourists, local or international in planning and organising their journey to Malaysian UNESCO World Heritage Sites. It is hoped that the outcome of this research not only be used in establishing the ‘UNESCO’ brand in Malaysia but also providing a guide to the travellers in their plan for a memorable journey.